Situation Report: Czechoslovakia, 15 December 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Four Czech Dissidents Released from Prison The Literary Scene on the Even of the Writers' Congresses How Much for Soviet Oil? New Brickyard: A Comecon Model Project The Christmas Market